Educational and home-environment asthma interventions for children in urban, low-income, minority families. (2nd December 2018) - Welker, Kristen; Nabors, Laura; Lang, Myia; Bernstein, Jonathan
ABSTRACT: Objective : This review examined the impact of environmental change and educational interventions targeting young children from minority groups living in urban environments and who were from low-income families. Data Sources : A scoping methodology was used to find research across six databases, including CINAHL, ERIC, PsycINFO, PubMed, MEDLINE, and EMBASE. Study Selection : 299 studies were identified. Duplicates were removed leaving 159 studies. After reviewing for inclusion and exclusion criteria, 23 manuscripts were identified for this study: 11 featured home-environment change interventions and 12 emphasized education of children. Results : Studies were reviewed to determine key interventions and outcomes for children. Both environmental interventions and educational programs had positive outcomes. Interventions did not always impact health outcomes, such as emergency department visits. Conclusions : Results indicated many of the environmental change and education interventions improved asthma management and some symptoms. A multipronged approach may be a good method for targeting both education and change in the home and school environment to promote the well-being of young children in urban areas. New research with careful documentation of information about study participants, dose of intervention (i.e., number and duration of sessions, booster sessions) and specific intervention components also will provide guidance for future research.